An operational model for capturing grape ripening dynamics to support harvest decisions - van Leeuwen, Cornelis; Destrac-Irvine, Agnès; Gowdy, Mark; Farris, Laura; Pieri, Philippe; Marolleau, Laura; Gambetta, Gregory A (OENO one, 2023)
Grape ripening is a critical phenological phase during which many metabolites that impact wine quality accumulate in the berries. Major changes in berry composition include a rapid increase in sugar and a decrease in malic acid content and concentration. Its duration is highly variable depending on grapevine variety, climatic parameters, soil type and management practices. Together with the timing of mid-veraison, this duration determines when grapes can be harvested.Viticulturists and winemakers monitor the sugar-to-total acidity ratio (S/TA) during grape ripening and start harvesting grapes when this ratio reaches the optimum value for the desired wine style. The S/TA ratio evolves linearly as a function of thermal summation during the first four weeks following the onset of ripening. The linearity of the evolution of the S/TA ratio as a function of thermal time during the first four weeks following mid-veraison is applied in this study on two large data sets encompassing (1) 53 varieties studied during 10 years with two to four replicates for each combination of year and cultivar and (2) two varieties, cultivated on three soil types over 13 years. Grape ripening speed is highly variable. The effects of the year impact ripening speed more than the effects of the soil or the variety, although all three effects are highly significant. Grape ripening speed decreases with berry weight and also varies with vine water status. By using this approach, viticulturists and winemakers can assess four weeks after mid-veraison, for each individual vineyard parcel, at what speed grape ripening progresses. Combined with precise mid-veraison scoring, expertise from previous vintages and complementary approaches like sensory assessment of berries, it allows harvest date estimates to be fine-tuned. The results of this study can also be used to identify slow ripening varies, which are better performing in warm climates and, thus, better adapted to climate change.